Micropolítica: práxis performativa entre cuidado, arte e erotismo - Ferreira, Jefferson Grochovski (2024)
This work is based on a cartographic practice of my experience between care, art and eroticism, with the production of deviant pornography, together with the EdiyPorn collective, of which I am part. Addressing issues experienced in the fields of art, eroticism, and care practices seeking to create openings for other ways of thinking and producing experiences. From a micropolitical perspective of deviant subjectivities, this writing looks out to the reverberations that these experiences produce in normative society. Therefore, it proved important to articulate the relation between the fields covered, which are independent, and which are potentialized when they are in relation. To this end, we seek to create, from these meetings, a common field, in which it is possible to articulate deviant pornography, art and care, and make this territory an act of creation